Evalution of endogenous intoxication in patients on herpesassociated multiforme exudative erythema - Shnaider, S. A.; Denisova, M. T.; Noneva, N. O. (Journal of Education, Health and Sport, 2017)
In this work the determination of the parameters of endogenous intoxication in patients herpes associated multiforme exudative erythema in the context of the severity of the disease compared with patients with exudative erythema multiforme other etiologies and patients with recurrent herpes simplex. Shown that patients herpes associated multiform exudative erythema of the oral cavity have a pronounced degree of endogenous intoxication, which is directly correlated with the degree of severity of the disease, which gives grounds for inclusion in the scheme of complex treatment of patients with herpeszoster bahatoformatne exudative erythema methods of detoxication therapy.